Amos Overheard: Amos 7:10–17, Its Addressees, and Its Audience - Davis, Andrew R. (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2022)
This article argues that the depiction of Amos in 7:10–17 reflects the post-exilic scribal turn in prophecy and was meant to legitimize this new mode of prophecy for Yehudite audiences. Much of the scholarship on 7:10–17 focuses on what Amos’s words meant to Amaziah and vice versa, but the addressees within the text are not the same as its actual audience. Within the text Amos’s words are addressed to Amaziah, but this article argues that their real audience consisted of rural Yehudites, who were meant to “overhear” the conversation and accept its new scribal version of Amos.